IDENTIFIKASI POTENSI BAHAYA KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PEMULUNG DI TEMPAT PEMBUANGAN AKHIR (TPA) TERJUN - Deli Syaputri; Samuel Marganda Halomoan Manalu; Theodorus Teddy Bambang Soedjadi; Risnawati Tanjung (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Potential hazards of Occupational Health and Safety at the Final Disposal Site have a hazard risk to the safety and health aspects of workers. This research is a qualitative research that aims to explore a problem with detailed boundaries, as wel as in-depth data collection. The number of informants in this study were 6 people. Data collection was carried out using direct observations conducted on workers and in-depth interviews with research respondents equipped with a voice recorder which was conducted to 6 informants. The results of the research conducted there are potential hazards that still need to be considered and controlled. There are several potential hazards that result in accidents and occupational diseases, namely: 1. Physical hazard factors, such as being pierced by sharp objects (thorns, nails, glass shards, waste baskets, gancu), slipping due to slippery roads and piles of garbage, falling, and noise. 2. Chemical hazard factors, such as toxic materials. 3. Ergonomic hazard factors, such as Musculoskeletal Disorder (MSDs), deformity. 4. Psychological hazard factors, such as pressure between scavengers. 5. Biological hazard factors, such as those caused by vectors and animals that disturb flies, rats, mosquitoes, cockroaches and fungi. 6. Environmental hazard factors, such as damaging the environment, air pollution, and soil pollution. 7. Behavioral hazard factors, such as not using masks and gloves, causing unsafe conditions and unsafe actions. Suggestions that can be given are to increase supervision of workers so that workers do not do things that can harm themselves or others, provide sanctions for workers who violate the rules, and equip workers with Personal Protective Equipment in accordance with their work.